2015
DOI: 10.1161/strokeaha.114.006849
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of White Matter Hyperintensities Differs in Hypertensive and Nonhypertensive Ischemic Stroke

Abstract: Background and Purpose Epidemiological studies suggest white matter hyperintensities (WMH) are extremely heritable but the underlying genetic variants are largely unknown. Pathophysiological heterogeneity is known to reduce the power of genome-wide association studies (GWAS). Hypertensive and non-hypertensive individuals with WMH might have different underlying pathologies. We used GWAS data to calculate the variance in WMH volume (WMHV) explained by common single nucleotide polymorphisms (SNPs) as a measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
1
30
1
2
Order By: Relevance
“…10 In the current study, we found no association signal with variants at 17q25. This might relate to differences in the protocols used for measuring WMH burden or to a differential impact of 17q25 region on WMH burden in normal elderly subjects and CADASIL.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…10 In the current study, we found no association signal with variants at 17q25. This might relate to differences in the protocols used for measuring WMH burden or to a differential impact of 17q25 region on WMH burden in normal elderly subjects and CADASIL.…”
Section: Discussioncontrasting
confidence: 68%
“…However, differentiating lacunes from other imaging findings, such as dilated Virchow-Robin spaces, may be difficult, 22 and a recent study in patients with acute ischemic stroke showed that the signals for WMH and lacunes do not necessarily overlap. 10 In conclusion, we found a polygenic risk score to be associated with WMH volume in CADASIL. Our results suggest that multiple genetic variants with small effect sizes influence WMH burden.…”
Section: April 2014mentioning
confidence: 56%
See 1 more Smart Citation
“…31 Discrepancy exists between high heritability estimates (>50%) for WMH obtained in twin and family history studies 32 and relatively low estimates (~25%) derived from genome-wide association studies. 33 A factor influencing such missing heritability is gene-environment interactions; thus, measuring environment rigorously and analyzing it against genome-wide association studies data could be a useful strategy. In fact, interaction between VRFs and gene expression could help explain part of the missing heritability, as WMH volume attributable to common genetic variants has been estimated to be 45% for hypertensives against 13% for nonhypertensives.…”
Section: Inflammation Infection and Brain-gut Axis In Svdmentioning
confidence: 99%
“…These approaches use distant relatedness between individuals to infer heritability and coheritability of complex traits and have been used to provide insights into and between many diseases 35, 36, 37. We performed a bivariate GREML analysis in two large GWAS cohorts consisting of AD and IS cases and controls to assess evidence of a shared genetic contribution to the two diseases.…”
mentioning
confidence: 99%